Correlation between Teacher’s Classroom Management and Students’ English Academic Achievement - Wa Ode Juniati; Samtidar Samtidar; Ahmad Talib (Journal of Excellence in English Language Education, 2022)
The study aimed to find out the correlation between teachers’ classroom management and students’ English academic achievement. This research employed quantitative research method. The subject of this research were the three classes of 3rd grade students of natural science at SMAN 2 Soppeng that consisted of 36 students which were taken by using cluster random sampling. The instruments used to collect data were a questionnaire and a test. According to the research findings in the questionnaire results, the four levels of classroom management were perceived by the students in varying numbers. There are 10 students (27.7%) who scored in the very high cluster, 14 students (39%) whose scored in the high cluster, 8 students (22.2%) who scored in the average cluster, and 4 students who scored in the low cluster (11.1%). In other word, teacher’s classroom management at SMAN 2 Soppeng was adequate. For their academic achievement, 28 students (78%) were in the very good cluster, while 1 student (2.7%) was in the good cluster, 2 students (5.5%) were in enough cluster, and 5 students (13.8%) were in poor cluster. From the data, it can be inferred that the score of Pearson Product Moment Correlation was found that there was a significant correlation between classroom management and students’ academic achievement in English subject at SMAN 2 Soppeng (r-.610). This means that classroom management have relationship toward students’ academic achievement.